1992
DOI: 10.1037/0021-843x.101.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Smooth-pursuit eye tracking in first-episode psychotic patients and their relatives.

Abstract: We wished to determine the specificity of smooth-pursuit eye tracking dysfunction to schizophrenia and the prevalences of dysfunction among functionally psychotic and normal individuals. Therefore, we investigated pursuit tracking in a large sample of psychotic patients, normal subjects, and first-degree relatives (N = 482). Patients were recruited as part of an epidemiological study of first-episode psychosis that used a broadly based referral network to identify all cases in a major metropolitan area over a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
109
3
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 148 publications
(124 citation statements)
references
References 54 publications
11
109
3
1
Order By: Relevance
“…Some studies have reported impaired smooth pursuit eye movements in bipolar patients (Shagass et al, 1974;Levin et al, 1981;Iacono et al, 1982;Holzman et al, 1984), whereas other studies showed no difference between affective disorder patients and controls (Holzman et al, 1974;Iacono et al, 1992;Friedman et al, 1995). Several studies found that relatives of affective disorder patients and controls did not differ in eye tracking performance (Levy et al, 1983(Levy et al, , 1993Rosenberg et al, 1997; but see Kathmann et al, 2003).…”
mentioning
confidence: 98%
“…Some studies have reported impaired smooth pursuit eye movements in bipolar patients (Shagass et al, 1974;Levin et al, 1981;Iacono et al, 1982;Holzman et al, 1984), whereas other studies showed no difference between affective disorder patients and controls (Holzman et al, 1974;Iacono et al, 1992;Friedman et al, 1995). Several studies found that relatives of affective disorder patients and controls did not differ in eye tracking performance (Levy et al, 1983(Levy et al, , 1993Rosenberg et al, 1997; but see Kathmann et al, 2003).…”
mentioning
confidence: 98%
“…As with smooth pursuit eye-tracking abnormalities~Iacono, Moreau, Beiser, Fleming, & Lin, 1992!, electrodermal nonresponsivity~Iacono, Ficken, & Beiser, 1999!, and neuroanatomical abnormalities~Sharma et al, 1997!, P300 reduction is seen in unaffected biological relatives of Figure 8. Event-related potentials~ERPs!…”
Section: Clinical Contributions To Broken P300mentioning
confidence: 99%
“…Pursuit is one of the important human skills that have been used, for example, to differentiate normal subjects from psychiatric patients [12,8,9] or to qualify a pilot [11,19]. Given the parts of the human body that are used, pursuit can be categorized into eye movement [13,3], locomotion [4], manual tasks [21], etc.…”
Section: Related Work 21 Pursuit Taskmentioning
confidence: 99%